Study of method validation on ramipril with reverse phase HPLC method - Radhika Ramidi; Lakkarasu Bhanu Chander (International Journal of Pharmacy and Analytical Research, 2022)
A new simple and precise reverse phase high performance liquid chromatographic method has been developed and subsequently validated for the estimation of Ramipril in bulk and its pharmaceutical dosage form. The chromatographic separation was performed by using mobile phase consisting of 0.01M KH2PO4: Acetonitrile in the ratio of 30:70 % v/v and the pH 2.8 adjusted with 0.2% orthophosphoric acid. The column used was Kromasil C18 (150×4.6 mm, 5µ) with flow rate of 1 ml/min using PDA detection at 210nm. The described method was found to be linear over the range of 5- 30µg/ml and correlation coefficient was found to be 0.999. The assay of Ramipril was found to be 100.80 %. The results of the study showed that the proposed RP-HPLC method is simple, rapid, precise, reliable, accurate and economical which is useful for the routine determination of Ramipril in bulk and its pharmaceutical dosage form.